Agus Moh. Najib’s Project and Ushul Fiqh Redesign: Interlinking of Islamic Law and Legal Sciece - Karimullah, Suud Sarim (UIN Sunan Kalijaga Yogyakarta, 2023)
This study devels into the transformational efforts of Agus Moh Najib, a prolific Muslim intellectual and professor of ushul fiqh at UIN Sunan Kalijaga Yogyakarta, in revitalizing and reforming the conceptual framework of ushul fiqh, which is the cornerstone of Islamic law in response to the complex challenges of modernity. The research conducted is a type of qualitative research with a descriptive-analytical review of various sources of literature that is equipped with a philosophical study through the data analysis method used is content analysis. The findings of this study highlight the ongoing process of redesigning ushul fiqh initiated by Agus Moh Najib is directed to bring closer and interconnect between Islamic law and legal science in general. He also sits the position of Islamic law in proportion between the sacred dimension and the profane dimension. Redesign of ushul fiqh as the foundation for jurisprudence and Islamic law is an urgent step to be done because the changing conditions and situations, time and place as a result of these factors, have invited a variety of serious problems related to jurisprudence and Islamic law. In contrast, the method of ijtihad developed by reformers of legal thinkers in answering various issues of modern times has not been satisfactory.[Penelitian ini mengupas upaya transformasional Agus Moh Najib, seorang intelektual muslim yang produktif dan guru besar ushul fiqh di UIN Sunan Kalijaga Yogyakarta, dalam merevitalisasi dan mereformasi kerangka konseptual ushul fiqh, yang merupakan landasan hukum dalam Islam guna menjawab berbagai tantangan modernitas yang begitu kompleks. Penelitian yang dilakukan adalah jenis penelitian kualitatif dengan tinjauan deskriptif analitik terhadap berbagai sumber pustaka yang dilengkapi dengan kajian filosofis melalui metode analisis data yang digunakan adalah content analysis. Temuan penelitian ini menyoroti proses konsep redesain ushul fiqh yang digagas oleh Agus Moh Najib diarahkan untuk mendekatkan dan menginterkoneksikan antara hukum Islam dan keilmuan hukum pada umumnya. Dia juga mendudukkan posisi hukum Islam secara proporsional antara dimensi sakral dan dimensi profan. Redesain ushul fiqh sebagai fondasi bagi fiqh dan hukum Islam merupakan langkah yang urgen untuk dilakukan sebab terjadinya perubahan kondisi dan situasi, waktu dan tempat sebagai akibat dari faktor-faktor tersebut, telah mengundang berbagai masalah serius berkaitan dengan fiqh dan hukum Islam. Sedangkan metode ijtihad yang dikembangkan para pembaharu pemikir hukum dalam menjawab berbagai problematika zaman modern saat ini belum juga memuaskan.]